Complexation reaction with Sm(III): a facile spectrophotometric quantification of daunorubicin in pharmaceutical preparation and biological fluids - Basima A. A. Saleem (Discover Chemistry)
Abstract Daunorubicin Hydrochloride considers the first anthracycline antibiotic widely used as a chemotherapeutic agent for various cancers, including acute myeloid leukaemia, acute lymphoblastic leukaemia, and Kaposi’s sarcoma. Monitoring daunorubicin levels during treatment is crucial due to its cardiotoxic effects, which correlate with the administered dose. Despite the importance of accurate measurements, published spectrophotometric methods for the determination of daunorubicin are limited, therefore, this study proposing a novel and rapid spectroscopic method based on the formation of a complex with samarium ions (III). The reaction mechanism involves the coordination of DanH with samarium, enhancing its detectability. Optimal conditions for the formation of the pink complex were established by studying various factors, including pH, time, samarium concentration, and temperature. The proposed method demonstrated a significant linear relationship between absorbance and daunorubicin concentration in the range of 1–48 µg/mL, with a correlation coefficient of 0.9974. Detection limits were established at 0.0025 and 0.0250 µg/mL. The relative standard deviations (RSD%) from multiple measurements of different DanH concentrations ranged from 0.022 to 0.039%, indicating high precision. Moreover, the method’s accuracy, selectivity, and robustness were confirmed through comparative analysis with existing methods. This technique has been successfully applied to determine DanH in various samples, including pharmaceutical preparation, urine, and serum.